Peran Komoditas Sawit Pada Perekonomian Bengkulu - Indraswanti, Bertha Iin Esti; Sunoto, Sunoto; Gunawan, Romi (Convergence: The Journal of Economic Development, 2023)
The purpose of this research was to analyze palm oil on economic of Bengkulu Province. Base on BPS secondary and primary data, descriftive analysis was used to analyze the palm oil contribution on economic of Bengkulu Province. Land area of palm oil is more 50% than all of plantation land area in Bengkulu. The high productivity of CPO, palm oil is very potential commodity to increase Bengkulu economic. There are strong and positive correlation between palm oil land area with income disparities over the regent/city, the poverty rate, and income percapita. Activities of Palm oil plantation in 2022 relatively stable, but respondent predict will increase on Triwulan IV-2022. The respondent optimism made a prediction of labor absorption increase. Positive impact of the business on society welfare create by employment multipier and income multiplier effect.   Keywords:  Palm oil, poverty.